Evaluación de enfermedades fungosas en tres clones de cacao bajo diferentes niveles de sombra en la Estación Experimental El Padmi - Carpio Balcázar, Damary Viviana (2023)
Theobroma cacao L is a crop that requires shade for its optimal physiological development and for protection from radiation, this same shade can have an impact on the incidence of diseases in cocoa, while dense shade can favor the spread of some pathogens, light shade or lack of shade can limit the development of others. Therefore, the present research project was carried out at El Padmi Experimental Station, with the purpose of diagnosing fungal diseases present in cocoa clones CCN-51, EETP-800 and EETP-801, under different levels of shade with the use of saran at intensities of 0 %, 35 % and 80 %. A Completely Randomized Design (CRD) with a bifactorial arrangement was applied, where Factor A corresponded to the varieties and Factor B to the shade levels. Parameters such as Incidence, Severity, Area Under the Disease Progress Curve (AUPC) and Disease Progress Rate (DPR) were evaluated. Assessments were performed every 15 days for 105 days. In addition, an interpolation of data was performed, using equations derived from a logarithmic regression for Incidence and Severity, new points were obtained based on data from day 1 to day 45, and an equation describing its curve up to day 105 was defined. The CCN-51 had an incidence ranging from 6.67 % to 26 %, the interpolated value indicates that it could reach 29 %, severity from 2.6 % to 20 %, the interpolated value indicates up to 23 %, ABCPE from 900 to 1 400, TPE of 0.04. While for clones EETP-800 and EETP-801 they had an incidence from 56.18 % to 68 %, the interpolated value indicates that it could reach 80 %, severity from 38 % to 57 %, the interpolated value indicates up to 63 %, AUPC from 4 000 to 5 000, TPE of 0.08. The results indicated significant differences in clone CCN-51 since it presented a lower Colletotrichum intensity compared to clones EETP-800 and EETP-801, the results obtained are independent of the level of shade applied, so that no significant differences were found in the shade factor. Key words: cocoa, fungal diseases, shade, Colletotrichum.